401 HYPERTENSION KNOWLEDGE IN URBAN BLACKS. Issue 1 (1st January 2007) - Sanne, S. S.; Muntner, P.; Kawasaki, L.; Hyre, A.; DeSalvo, K. B.
Abstract : Purpose: Poor hypertension knowledge may contribute to low rates of blood pressure control. The purpose of this study was to determine levels and correlates of hypertension knowledge among an urban, black population. Methods: Study participants with established hypertension ( n = 263) were administered a telephone survey, designed for low-literacy populations. Hypertension knowledge was assessed through a validated 10-item questionnaire on which respondents received 1 point for a correct response for a total possible score of 10. Results: The majority of participants were female (80.2%), 75% reported incomes less than $1, 000/month, 60% had at least a high school education, and 75% of respondents were reported always being comfortable asking their doctors questions. Overall, 40% of participants correctly answered 9 or 10 questions. Items with the lowest percentage of correct responses included knowing that a blood pressure of 130/80 is normal (58.9% correct), hypertension lasts a lifetime (59.3%), hypertension does not cause cancer (40.3%), and renal failure is a complication of hypertension (77.6%). Compared with their counterparts with a high hypertension knowledge score (9 or 10 questions correct), the odds ratio of a low hypertension knowledge score (< 8 questions correct) was 1.41 (95% CI 1.01, 1.96) for each 10 years older age, 1.81 (0.93, 3.52) for participants with less than a high school education, and 6.54 (1.93, 22.1) and 2.67 (1.22, 5.84) for participants initially diagnosed with hypertension within 1 year and 1 to 4 years ago, respectively, compared with 5 or more years in the past. Also, participants who reported sometimes and never being comfortable asking their doctor questions were 1.72 (95% CI 0.82, 3.62) and 2.06 (95% CI 0.39, 10.8) times more likely to have low hypertension knowledge compared with their counterparts who were always comfortable asking questions. Conclusions: Overall knowledge of high blood pressure was good in this population. However, deficits exist in specific content areas and certain subgroups. Effectively targeting hypertension education content to specific audiences and topical areas may improve hypertension knowledge for black patients receiving care in urban public hospitals.